Community Support For Divorced Women: A Study In Riau Province - Nelli, Jumni; Lubis, Sobhan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This paper aims to demonstrate how the Malay community's perspective on divorce once stigmatized for women and now supported by the community has changed. This study is essential in answering why Riau Malay women file for divorce, how the Riau Malay community feels about the occurrence of female divorce, and how public perceptions of female divorce affect them. The exchange theory, which emphasizes the analysis of costs and rewards in executing rights and obligations as husband and wife, was used to perform this field study on the Malay community in Riau province. According to the study's findings, women choose to file for divorce for several reasons. Because their husbands abandoned them for an extended period, 60 percent of women do not have husbands. The community does not support divorce, according to preliminary field data. However, the perception that society accepts divorce proposals from women has changed in light of what actually occurred. According to exchange theory analysis, husband-wife interactions will be harmonious if each person receives a reward for the cost incurred. In this case, the rights exchanged and duties assumed are equal. If there is an imbalance, it will impact the community's perception that women equally have the right to divorce. As a result, the Riau Malay community's perspective on women filing for divorce, which was previously frowned upon, has changed to one of support